Genomic characterization of multidrug-resistant Escherichia coli isolated from gills of Labeo rohita: Insight into resistome, virulence and pathogenicity - Amit Kumar; Rahul Singh; Asma Masood; Dhouha Choukaier; Abhinav Kumar; Ankit Dilipkumar Oza; Denekew Alemayehu Alamneh (PLoS ONE, 2026)
Antibiotic resistance in aquaculture settings is an emerging issue that threatens animal and human health. In this work, a multidrug-resistant (MDR) Escherichia coli strain (RG3) was isolated from the gill of Labeo rohita obtained from a retail fish market in Punjab, India. Antimicrobial susceptibility testing revealed resistance to various antibiotic groups, with intermediate susceptibility to imipenem. Whole-genome sequencing produced a 3.70 Mb draft genome with 3,814 genes and 39 resistance determinants. Genome analysis identified a chromosomally encoded multidrug resistance phenotype, including β-lactam resistance and efflux-mediated mechanisms, together with virulence factors associated with iron acquisition, biofilm formation, and host colonization. No plasmids were predicted in the short-read assembly. Genome-based prediction suggested a high likelihood of human pathogenicity and assigned the isolate to sequence type ST8020. This study aimed to characterize an MDR E. coli from an aquaculture source using phenotypic and genomic approaches. The identification of a chromosomally encoded resistome together with virulence-associated traits highlights the potential of aquaculture-derived E. coli to act as reservoirs of antimicrobial resistance within a one health framework.